Supporting Young Children's Behaviour Skills - Barnardos (Barnardo's,Ireland, 2016)
The early years is a critical period for social and emotional learning. Early years educators play a central role in supporting children to develop the skills required to understand and manage their emotions and be accepted by and play well with their peers. This book gives guidance on how to support the development of children's behaviour skills.